Experience-induced plasticity of thalamocortical axons in both juveniles and adults - Wimmer, Verena C.; Broser, Philip Julian; Kuner, Thomas; Bruno, Randy M. (The journal of comparative neurology, 2010)
We examined the effect of sensory deprivation on thalamocortical (TC) projections to the rat primary somatosensory cortex at different postnatal ages ranging from P0 to P96. Rats had their whiskers clipped off with one or two vibrissae spared. TC axons innervating barrel cortex were specifically labeled by injecting virus expressing fluorescent proteins into the corresponding primary (VPM) and/or secondary (POm) thalamic nuclei. The density of VPM axons in deprived columns was ≈34% lower relative to spared columns with a concomitant decrease in bouton density, suggesting a deprivation-induced retraction of VPM axons. Axonal changes were reversible upon regrowth of the clipped whiskers and independent of age at deprivation, indicating the absence of a critical period for anatomical plasticity. The POm projection was not obviously altered by sensory deprivation. We suggest that retraction and regrowth of TC axons substantially contribute to long-term deprivation-dependent functional plasticity. J. Comp. Neurol. 518:4629-4648, 2010. © 2010 Wiley-Liss, Inc.
First published: 26 August 2010
Gesehen am 26.02.2024